Direct oral anticoagulants and the risk of osteoporotic fractures in patients with non-valvular atrial fibrillation. (April 2021) - Kuo, Liang-Tseng; Lin, Su-Ju; Wu, Victor Chien-Chia; Chang, Jung-Jung; Chu, Pao-Hsien; Lin, Yu-Sheng
Background: The incidence of osteoporotic fracture increases with age, particularly in elderly populations with atrial fibrillation (AF). However, direct oral anticoagulants (DOACs) have less effect on osteoporotic fracture than vitamin K antagonists, it is unclear whether the risk of osteoporotic fracture is affected by different types and doses of DOACs in AF patients. Methods: This nationwide population-based cohort study included AF patients prescribed DOACs between 2011 and 2016 taken from the Taiwan National Health Insurance database. Adjusted hazard ratios (aHRs) for the risk of osteoporotic, hip, and spine fractures between DOAC users were compared using the Fine and Gray subdistribution hazard model to adjust for possible confounders. Results: A total of 56, 795 patients who were prescribed DOACs were included in the present study. Among them, 24, 597 patients received dabigatran, 26, 968 received rivaroxaban, and 5230 received apixaban. After 2 years' follow up, there was no significant difference in the incidence of osteoporotic, spine, or hip fracture among those receiving dabigatran, rivaroxaban, or apixaban. Subgroup analysis showed that patients taking dabigatran had a higher incidence of osteoporotic and hip fracture than those taking rivaroxaban and apixaban in cases with concomitant peripheral artery disease (PAD) or a history of hip fracture ( p for interaction: 0.004 and 0.030, respectively). However, dabigatran users had a lower incidence of osteoporotic fracture and spine fracture in those receiving standard-dose DOACs compared with rivaroxaban and apixaban; whereas, they had a higher incidence of hip fractures when administered at low dose. Conclusion: AF patients with different DOACs did not have different risks of osteoporotic fracture overall. However, additional concomitant morbidities, such as PAD or a history of hip fracture, and standard/low doses might be associated with different risks for different DOACs. These findings should be taken into consideration in the clinic when the DOAC is being chosen. Plain language summary: Different direct oral anticoagulants had different impact on osteoporotic fracture Anticoagulation therapy is an essential therapy in atrial fibrillation (AF) patients, but osteoporotic fracture is another important issue in these patients prescribed with anticoagulants. However, no study has been conducted to evaluate the impact of different DOACs on different types of osteoporotic fractures. In our findings, although different DOACs had no significantly different impact on osteoporotic fractures, dabigatran users had a slightly higher incidence of osteoporotic and hip fractures among different DOACs, particularly in those have simultaneously had peripheral artery disease, a history of hip fracture. In addition, when AF patients taking low-dose DOACs, dabigatran users also have higher incidence of hip fracture than those taking other DOACs.